Intergroup contact and endorsement of social change motivations: The mediating role of intergroup trust, perspective-taking, and intergroup anxiety among three advantaged groups in Northern Cyprus, Romania, and Israel. (January 2021) - Çakal, Huseyin; Halabi, Samer; Cazan, Ana-Maria; Eller, Anja
Three studies investigated the effect of intergroup contact and social identification on social change among three advantaged groups in Cyprus, Romania, and Israel. In Study 1 ( n = 340, Turkish Cypriots), intergroup contact with disadvantaged immigrant Turks positively predicted endorsement of their social change motivations directly, and via intergroup trust and perspective-taking indirectly. In Study 2 ( n = 200, Romanians), contact with the ethnic minority Hungarians positively predicted endorsement of their social change motivations via intergroup trust, perspective-taking, and intergroup anxiety, while ingroup identification negatively predicted endorsement of Hungarian ethnic minority's collective action tendencies via perspective-taking and anxiety. In Study 3 ( n = 240, Israeli Jews), intergroup contact positively predicted, while ingroup identification negatively predicted, endorsement of disadvantaged Israeli Palestinian citizens' social change motivations via perspective-taking, anxiety, and trust. Across three studies, results show that intergroup contact led the advantaged groups to attitudinally support social change motivations of the disadvantaged outgroups through increased trust, perspective-taking, and reduced anxiety, whereas ingroup identification weakened their intention to support social change motivations via perspective-taking and intergroup anxiety in Study 2, and via intergroup trust, perspective-taking, and intergroup anxiety in Study 3.